Antimalarial Activity of Ethanol Extract of Noni Leaves (Morinda citrifolia) towards Parasitemia, Splenomegaly, and Hepatomegaly in Plasmodium berghei ANKA Infected Mice - Putri Rahayu; Yetti Hernaningsih; Heny Arwati (Biomolecular and Health Science Journal, 2021)
Introduction: Malaria is one of the infectious diseases found in tropical countries and sub-tropical countries. In 2016 there were an estimated 445,000 people died to malaria. Alternative medicine is needed, such as natural based ingredient. Morinda citrifolia or noni plant is a medicinal plant found in all parts of Indonesia which has many benefits, such as antibacterial, analgesic, anticancer, antioxidant, and anti-inflammatory. The aims of this study were to determine the antimalarial activity of ethanol extract of noni leaves and its effect on splenomegaly and hepatomegaly.Methods: Extract of noni leaves was prepared by maceration using ethanol solvent. In vivo experiments were conducted using Plasmodium berghei infected BALB/c mice treated with the doses of 100, 10, 1 mg/kg body weight(BW) orally of ethanolic extract of noni leaves. Then, the percentage of parasitemia was calculated from day 1 to day 4 after treatment and at the end of the test, mice were sacrificed then spleen and liver were collected. Results: The highest parasite growth was found in the group treated with noni leaves ethanol extract at a dose of 1 mg/kg WB and vice versa. Probit analysis resulted in ED50 was 0.882 mg/kg WB. Spearmen test showed there was no correlation between doses and the size of splenomegaly with p=0,2 and between doses and the size of hepatomegaly with p=0,6.Conclusion: Ethanol extract of noni leaves possessed antimalaria activity and there was no correlation between doses of extract and t he splenomegaly and hepatomegaly.